2010
DOI: 10.1002/adsc.201000430
|View full text |Cite
|
Sign up to set email alerts
|

Selective Green Coupling of Alkynyltins and Allylic Halides to Trienynes via a Tandem Double Stille Reaction

Abstract: The palladium-catalyzed reaction of alkynyltin compounds with allylic chlorides leads to a 2:2 coupling to give trienynes by regio-and stereoselective formation of three new C À C bonds. The reaction can be applied to different alkynyl and allylic fragments, providing a wide range of trienynes with different substitution patterns in very good yields. They can be prepared in a green way using recyclable polymeric tin alkynyls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 24 publications
(8 reference statements)
0
16
0
Order By: Relevance
“…We chose to utilize Stille coupling instead of Sonogashira coupling because we had previously found that this method gives higher yields for installing phenylethynyl pyrrolic substituents [9]. The fluorinated tributyltinphenylacetylene analogs for the synthesis of L3 and L4 were synthesized according to literature procedures and used without purification [3536]. The Stille cross coupling reactions for the synthesis of L3 and L4 were monitored by MALDI–TOF–MS and were found to not be complete after increasing the reaction time to 48 h, so the reaction time was increased to 96 h with the addition of more catalyst and tributyltin reactant after 48 h. These modifications were deemed necessary to push the reaction towards completion and aid in purification of the free ligand.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose to utilize Stille coupling instead of Sonogashira coupling because we had previously found that this method gives higher yields for installing phenylethynyl pyrrolic substituents [9]. The fluorinated tributyltinphenylacetylene analogs for the synthesis of L3 and L4 were synthesized according to literature procedures and used without purification [3536]. The Stille cross coupling reactions for the synthesis of L3 and L4 were monitored by MALDI–TOF–MS and were found to not be complete after increasing the reaction time to 48 h, so the reaction time was increased to 96 h with the addition of more catalyst and tributyltin reactant after 48 h. These modifications were deemed necessary to push the reaction towards completion and aid in purification of the free ligand.…”
Section: Resultsmentioning
confidence: 99%
“…ADP, ADPI 2 , WS3, BF 2 (WS3), and Zn(WS3) 2 were synthesized and purified according to literature procedures with minor modifications [2,5,9,3334]. (4-Fluorophenylethynyl)tributyltin (for the synthesis of L3), and [4-(trifluoromethyl)phenyl](tributyltin)acetylene (for the synthesis of L4) were synthesized according to literature procedures with minor modifications and used without purification [3536]. …”
Section: Methodsmentioning
confidence: 99%
“…NMR spectra were recorded at rt with Bruker AM 250, DPX 250, Avance II 300, Avance 400 and Avance III HD 500 spectrometers. Chemical shifts are referenced to (residual) solvent signals ( 1 H/ 13 46 4-(trimethylsilyl)pyrazole, 47 and 3,5-di(tert-butyl)pyrazole 48 are literature known; the amount of OEt 2 present in the samples of Li 2 [1,1′-fc(BH 3 ) 2 ]·(OEt 2 ) 0.25 after prolonged storage in a screwcapped vial in the glove-box was determined by 1 H NMR spectroscopy.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Norbornenes are extremely convenient monomers for the targeted design of polymer materials with desired properties owing to their availability and the capability to polymerize via different ways. Polymers from substituted norbornenes could possess various valuable properties depending on the substituent nature, such as high glass transition temperatures, optical transparency, high gas permeability, low moisture absorption, the inertness of main chains, and so on. Usually norbornenes obtaining by Diels‐Alder reaction are mixtures of exo‐ and endo‐ isomers .…”
Section: Introductionmentioning
confidence: 99%